THE INFLUENCE OF TIKTOK LEARNING MEDIA ON INCREASING STUDENT LEARNING OUTCOMES IN CIVICS EDUCATION SUBJECTS IN CLASS X OF MUHAJIRIN IT VOCATIONAL SCHOOL - Risa Nursafitri; Tetep; Odang Hermanto (Journal Civics And Social Studies, 2024)
This research aims to determine the effect of Tiktok learning media on improving student learning outcomes in Civics subjects in class X SMK IT Muhajirin. This research uses quantitative methods with a Pre-Experimental research design (One Group Pretest- Posttest). Data collection techniques through documentation and tests. Documentation is carried out by collecting various data in the form of school administration file data and images that support this research. The test is carried out with questions given during the pretest and posttest. The population in the study was 5 class X skills with a total of 142 students. The sample in this research was students in class X TKJ 1, totaling 35 people using a purposive sampling technique. The instrument used is a multiple choice test with 20 items that have been validated. The data analysis technique uses the Normality test, the N-Gain Test to determine the increase in learning outcomes and the t test to test the hypothesis. The research results show that the average student score is 55.14, which means it is still below the KKM score (75). However, after being given learning treatment using the Tiktok learning media, the average student score was 77.59, meaning it had exceeded the KKM (75). After carrying out the N-Gain test, 20% of the values ​​were high interpretation, 66% were medium interpretation and 14% were low interpretation. Meanwhile, for hypothesis testing, a sig of 0.00 was obtained, which means <0.5. So there is an influence of Tiktok learning media on improving student learning outcomes in Civics subjects in class X Muhajirin IT Vocational School.